The role of Tcfap2c in tumorigenesis and cancer growth in an activated Neu model of mammary carcinogenesis - Park, JM (Oncogene, 2015)
TFAP2C/AP-2γ influences development of the mammary gland and regulates patterns of gene expression in luminal and HER2-amplified breast cancer. The roles of TFAP2C in mammary gland tumorigenesis and in pathways critical to cancer progression remain poorly understood. To gain greater insight into oncogenic mechanisms regulated by TFAP2C, we examined mammary tumorigenesis in MMTV-Neu transgenic female mice with or without conditional knockout (KO) of Tcfap2c, the mouse homolog of TFAP2C. Loss of Tcfap2c increased the latency of tumorigenesis and tumors that formed demonstrated reduced proliferative index and increased apoptosis. In addition, tumors formed in Tcfap2c KO animals had a significant reduction in Egfr levels without a change in the expression of the Neu oncogene. The MMneu-flAP2C cell line was established from tumor tissue derived from MMTV-Neu/Tcfap2c(L/L) control animals and parallel cell lines with and without expression of Tcfap2c were created by transduction with adenovirus-empty and adenovirus-Cre, respectively. KO of Tcfap2c in vitro reduced activated phosphorylated-Erk, decreased cell viability, repressed tumor growth and was associated with attenuation of Egfr expression. Chromatin immunoprecipitation and direct sequencing and expression analysis confirmed that Egfr was a Tcfap2c target gene in murine, as well as human, mammary carcinoma cells. Furthermore, decreased viability of mammary cancer cells was directly related to Egfr functional blockade. We conclude that TFAP2C regulates tumorigenesis, cell growth and survival in HER2-amplified breast cancer through transcriptional regulation of EGFR. The findings have important implications for targeting the EGFR pathway in breast cancer.